2022
DOI: 10.1177/14799731221119810
|View full text |Cite
|
Sign up to set email alerts
|

The prognosis of pre-frail chronic obstructive pulmonary disease patients for hospitalizations and mortality depends on their level of functional physical performance

Abstract: Objective To determine if pre-frail Chronic obstructive pulmonary disease (COPD) patients with poor and non-poor performance in the five-repetition sit-to-stand test (5-STS) had a worse prognosis for hospitalization and mortality at 2 years and for mortality at 5 years than non-frail patients. Methods We prospectively included patients with stable COPD, between 40 and 80 years, from a hospital in Spain. Patients were classified according their performance on the 5-STS test and level of frailty. Timing, number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The studies reported a fall rate of up to 50% in this population. The presence of balance deficits and gait disturbances has been identified as a significant risk factor for falls in COPD patients [59][60][61][62]. Furthermore, the long-term alteration of posture (breathing at a high lung volume [hyperinflated lungs], which causes a slight backward displacement of the thorax and high shoulder position), muscle dysfunction, and the use of steroids, may lead to breathing and gait disturbances [12,63].…”
Section: Explanation Of Gait Disturbance and Its Significance In Copd...mentioning
confidence: 99%
See 1 more Smart Citation
“…The studies reported a fall rate of up to 50% in this population. The presence of balance deficits and gait disturbances has been identified as a significant risk factor for falls in COPD patients [59][60][61][62]. Furthermore, the long-term alteration of posture (breathing at a high lung volume [hyperinflated lungs], which causes a slight backward displacement of the thorax and high shoulder position), muscle dysfunction, and the use of steroids, may lead to breathing and gait disturbances [12,63].…”
Section: Explanation Of Gait Disturbance and Its Significance In Copd...mentioning
confidence: 99%
“…The integration of social robots in rehabilitation can have benefits and distinct advantages. One advantage is one-on-one support; social robots provide personalized support, enabling healthcare professionals to dedicate more time and attention to individual patient needs [59]. Also, robots can be utilized as a tool for gait assessment, complementing traditional methods and providing valuable data for healthcare professionals to analyze and tailor treatment plans accordingly [63].…”
Section: Explanation Of Gait Disturbance and Its Significance In Copd...mentioning
confidence: 99%